Clinical and Cost-Effectiveness of Personalized Tele-Based Coaching for Farmers, Foresters and Gardeners to Prevent Depression: Study Protocol of an 18-Month Follow-Up Pragmatic Randomized Controlled Trial (TEC-A) - Thielecke, Janika; Buntrock, Claudia; Titzler, Ingrid; Braun, Lina; Freund, Johanna; Berking, Matthias; Baumeister, Harald; Ebert, David D. (Frontiers in Psychiatry, 2020)
Background: Farmers show high levels of depressive symptoms and mental health problems in various studies. This study is part of a nationwide prevention project carried out by a German social insurance company for farmers, foresters and gardeners (SVLFG) to implement internet- and tele-based services among others to improve mental health in this population. The aim of the present study is to evaluate the (cost-)effectiveness of personalized tele-based coaching for reducing depressive symptom severity and preventing the onset of clinical depression, compared to enhanced treatment as usual. Methods: In a two-armed, pragmatic randomized controlled trial (N=312) with follow-ups at post-treatment (6 months), 12 months and 18 months, insured farmers, foresters and gardeners, collaborating family members and pensioners with elevated depressive symptoms (PHQ-9 ≥ 5) will be randomly allocated to personalized tele-based coaching or enhanced treatment as usual. The coaching is provided by psychologists and consists of up to 34 tele-based sessions for 25 to 50 minutes delivered over 6 months. Primary outcome is depressive symptom severity at post-treatment. Secondary outcomes include depression onset, anxiety, stress and quality of life. A health-economic evaluation will be conducted from a societal perspective. Discussion: This study is the first pragmatic randomized controlled trial evaluating the (cost-) effectiveness of a nationwide tele-based preventive service for farmers. If proven effective, the implementation of personalized tele-based coaching has the potential to reduce disease burden and health care costs both at an individual and societal level. Trial registration: German Clinical Trial Registration: DRKS00014000.